Development of the Indonesian sexual quality of life scale for women (ISQOL-W) - Hadiprajitno, Peter I.; Ediati, Annastasia; Ariani, Mahayu D.; Muniroh, Muflihatul; Juniarto, Achmad Z. (Narra Sains Indonesia, 2024)
Sexual quality of life is greatly influenced by sexual function, yet thorough measures remain limited and vary across regions. In Indonesia, diverse cultural and religious contexts notably shape sexual quality of life. Thus, it is important to have a tool that considers both internal and external aspects. The aim of this study was to develop a valid and reliable scale that specifically measures Indonesian sexual quality of life for women (ISQOL-W), considering cultural and social factors. A total of 228 participants were recruited from April 30, 2023, to September 30, 2023. The ISQOL-W was developed through two phases: item generation and psychometric evaluation. In the first phase, 68 items were drafted based on definitions and dimensions of sexual quality of life. In the second phase, exploratory factor analysis resulted in 34 items with a loading factor greater than 0.4 (ranging from 0.41 to 0.84) which were categorized into four domains/factors: sexual-related emotion, sexual fantasy, sexual arousal, and sexual relationship. The Cronbach’s α coefficient for the overall questionnaire was 0.915, with subscale reliability ranging from 0.826 to 0.903. Further analysis revealed significant differences in ISQOL-W scores across relationship status, educational level, history of last sexual activity, and type of sexual activity. In conclusion, the ISQOL-W demonstrated robust psychometric properties, supporting its use in future studies. This study represents the first effort to develop and validate a sexual quality of life scale specifically for Indonesian women.